2020
DOI: 10.1002/hed.26428
|View full text |Cite
|
Sign up to set email alerts
|

Utility of narrowband imaging in the diagnosis of laryngeal leukoplakia: Systematic review and meta‐analysis

Abstract: This systematic review and meta-analysis evaluates the validity of narrowband imaging (NBI) in differentiating between low-risk leukoplakia and high-risk leukoplakia. Medline, EMBASE, Scopus, Cochrane Database of Systematic Reviews and Database of Abstracts of Reviews of Effects were searched. Studies evaluating the diagnostic accuracy of NBI in the assessment of laryngeal leukoplakia were included. Pooled sensitivity, specificity and diagnostic odds ratio were calculated. Seven studies met the inclusion crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
3
1
Order By: Relevance
“…10 In our study, using the Ni classification (2011 classification in cases without glottic leucoplakia and 2019 classification in cases with leucoplakia), we found that the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for narrow-band imaging to identify vocal fold lesions as benign or malignant was 91.9 per cent, 93.8 per cent, 97.1 per cent, 83.3 per cent and 92.5 per cent, respectively. It is likely that the higher specificity found in our study, compared with that of Ahmadzada et al 17 In 2018, Šifrer et al studied 40 patients, and reported the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for narrow-band imaging to predict malignancy using the European Laryngeal Society classification as 100 per cent, 95 per cent, 88 per cent, 100 per cent and 96 per cent, respectively. 18 In 2020, Šifrer et al conducted another study, with a larger sample size of 144 cases, to further investigate the effectiveness of the European Laryngeal Society classification.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…10 In our study, using the Ni classification (2011 classification in cases without glottic leucoplakia and 2019 classification in cases with leucoplakia), we found that the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for narrow-band imaging to identify vocal fold lesions as benign or malignant was 91.9 per cent, 93.8 per cent, 97.1 per cent, 83.3 per cent and 92.5 per cent, respectively. It is likely that the higher specificity found in our study, compared with that of Ahmadzada et al 17 In 2018, Šifrer et al studied 40 patients, and reported the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for narrow-band imaging to predict malignancy using the European Laryngeal Society classification as 100 per cent, 95 per cent, 88 per cent, 100 per cent and 96 per cent, respectively. 18 In 2020, Šifrer et al conducted another study, with a larger sample size of 144 cases, to further investigate the effectiveness of the European Laryngeal Society classification.…”
Section: Discussioncontrasting
confidence: 51%
“…In 2020, Ahmadzada et al reported the sensitivity, specificity, negative likelihood ratio and positive likelihood ratio of narrow-band imaging in diagnosing laryngeal cancer using the Ni 2011 classification as 95.0 per cent, 83.3 per cent, 0.06 and 5.76, respectively. 17 As per the Ni 2019 classification, the sensitivity, specificity, positive predictive value and negative predictive value for the diagnosis of suspicious lesions with leucoplakia under narrow-band imaging was 82.6 per cent, 92.8 per cent, 73.1 per cent and 95.7 per cent, respectively. 10 In our study, using the Ni classification (2011 classification in cases without glottic leucoplakia and 2019 classification in cases with leucoplakia), we found that the sensitivity, specificity, positive predictive value, negative predictive value and accuracy for narrow-band imaging to identify vocal fold lesions as benign or malignant was 91.9 per cent, 93.8 per cent, 97.1 per cent, 83.3 per cent and 92.5 per cent, respectively.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…A higher score indicates more serious vocal fold vibration asymmetry. The vocal fold mucosal wave was divided into 0-5 points, and a higher score indicates more serious disappearance of vocal fold mucosal wave [11]. Based on electronic pathology and outpatient reexamination records, the cumulative recurrence rate of patients within one year was calculated.…”
Section: Outcome Measuresmentioning
confidence: 99%